2021
DOI: 10.3390/pharmaceutics13101664
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Freezing Phenomenon in Vials Using an Infrared Camera

Abstract: The freezing phenomenon has a dramatic impact on the quality of freeze-dried products. Several freezing models applied to solutions in vials have been proposed to predict the resulting product morphology and describe heat transfer mechanisms. However, there is a lack of detailed experimental observations of the freezing phenomenon in vials in the literature. Thus, the present work offers new experimental observations of the freezing phenomenon in vials by infrared (IR) thermography. IR imaging allowed each via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Van Bockstal et al reported on the use of an IR camera to monitor rotating glass vials [ 14 ]. In another publication, freezing behaviour inside glass vials was also studied using an infrared camera [ 19 ]. Correct temperature readings were obtained as also shown here, but without high thermal and spatial resolution to reveal more subtle differences [ 14 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Van Bockstal et al reported on the use of an IR camera to monitor rotating glass vials [ 14 ]. In another publication, freezing behaviour inside glass vials was also studied using an infrared camera [ 19 ]. Correct temperature readings were obtained as also shown here, but without high thermal and spatial resolution to reveal more subtle differences [ 14 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another publication, freezing behaviour inside glass vials was also studied using an infrared camera [ 19 ]. Correct temperature readings were obtained as also shown here, but without high thermal and spatial resolution to reveal more subtle differences [ 14 , 19 ]. In Figure 2 a–d, spatial contour plots of the germanium and glass windows are shown for the oil–water experiment after 0 and 180 s, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is extremely useful for automatizing the controlled-freezing protocol, as the presence of an operator is not required if the values of P n and t n are already known. Moreover, this is a necessary requirement for a whole batch, where most of the vials are not in-sight of the operator, and the only way to properly select the nucleation pressure and time is by means of prior knowledge (as in this work), or alternatively, through the use of a suitable monitoring device (for instance, heat flux sensors [41] or infrared thermography [42] that were recently applied to the VISF protocol).…”
Section: Optimized Vacuum Induced Surface Freezing Conditions For Freeze-dryingmentioning
confidence: 99%